Electrochemical stability of laser shock peened 17-4 PH stainless steel. (December 2019) - Karthik, D.; Swaroop, S.
Highlights: Peening increased the surface roughness and oxidation slightly. Peening induced roughness insignificantly influenced the corrosion behavior. Melted/re-solidified layer improved corrosion resistance of 17-4 PH SS by suppressing the deleterious inclusions. Presence of δ-ferrite phase in the martensite matrix promoted the pitting corrosion rate. Abstract: In this study influence of laser shock peening without protective coating (LSPwC) on electrochemical stability of 17-4 PH martensitic stainless steel was investigated using potentiodynamic polarization and electrochemical impedance spectroscopy techniques. For this purpose room-temperature LSPwC was performed with laser pulses of 10 ns duration at two pulse densities (2500 and 6250 pulses cm −2 ). LSPwC increased the surface roughness to a maximum of 1.1 μm, influenced by material-ablation during peening and the peened surfaces showed slight enhancement in oxidation. Corrosion behavior in 3.5% NaCl solution was found to be insignificantly influenced by peening induced surface roughness. On the peened surfaces due to melted/re-solidified layer no deleterious inclusions were found and thereby the charge transfer resistance was improved. Peening did not suppress the secondary δ-ferrite phase in the martensite matrix, which acted as strong pit initiators. Pitting corrosion occurred preferentially at the regions where δ-ferrite phase present both at unpeened and peened conditions. Morphology of the pits formed on peened conditions is discussed.